Role models [compact disc, unabridged] - Waters, John, 1946- (Tantor Audio, 2010)
Filmmaker John Waters presents a self-portrait told through intimate profiles of favorite personalities, from Esther Martin, owner of the scariest bar in Baltimore, to the insane martyr Saint Catherine of Siena.